Operationalizing the Science of Delivery Agenda to Enhance Development Results - Gonzalez Asis, Maria; Woolcock, Michael (Washington, DC: World Bank, 2015)
The clear development gains achieved in recent decades should not defl ect attention from the scale and type of challenges that remain. The s trategies largely responsible for these initial gains have been techni cal reforms promoting economic growth and logistical systems supplying basic inputs. Today, strategies are needed that focus on enhancing th e quality of implementation— for example, ensuring learning and not ju st building schools and enrolling students. This concern now spans num erous domains of professional practice (especially health) and has ent ered World Bank discussions framed as the “science of delivery.” At th e World Bank, the Global Delivery Initiative (GDI) is an operational m anifestation and extension of these ideas. To date, the GDI has prepar ed a number of different case studies across numerous sectors on ways in which innovative teams solve particular problems during project imp lementation. On the basis of the initial case studies, the authors out line five key principles of how high-quality implementation occurs and invite others to add to this growing storehouse of knowledge. Specifi cally, task teams are encouraged to develop “live” case studies by and for their staff, documenting how, in real time, implementation challe nges are being met. Projects must “learn” more rapidly and systematica lly how to solve the myriad range of complex implementation challenges they inevitably encounter, since most of these (by definition) cannot be anticipated ex ante. Delivery challenges of this kind will only in tensify in the coming years as citizens demand effective responses to ever-more complex—and contentious—policy domains, such as justice, reg ulation, and taxation.